Kapabilitas Dinas Kesehatan Provinsi Riau Dalam Mencegah Peningkatan Positivity Rate Covid-19 Varian Omicron di Provinsi Riau Tahun 2022 - Nurul Mutmainnah Jamil; Dyah Vinianti; Nadhila Adhani (PendIPA Journal of Science Education, 2022)
The cause of COVID-19, namely SARS-CoV-2, continues to mutate form a new variant. The latest variant that has been detected, namely variant Omicron or known as variant B.1.1.529, has a speed of high transmission rate up to 5 times that of the previous variant, including Delta variant. Since the last peak of daily Covid-19 cases was in July 2021 hits 56,000 new cases per day, for the first time in 2022 new case rate hits 64,147 positive confirmed cases as of 16 February 2022, especially in Riau Province, there was an additional of new active cases 539. This figure is considered quite high because Riau Province is included in the top 10 province with the highest number of positive cases at this time. The purpose of this research is to analyze the capacity of the Riau Provincial Health Office in preventing a drastic increase in the positive rate. Based on research results the capacity of the Riau Provincial Health Office in preventing an increase in the positivity rate The omicron variant focuses on mitigation and preparedness enhancement including: (1) promotion of healthy lifestyles and tightening of 3M implementation, (2) restrictions community activities, (3) acceleration of vaccines and, (4) provision of facilities and infrastructure hospital. The conclusion in this research despite the Covid-19 prevention the omicron variant is already quite good in Riau Province, some efforts are needed increased by the local government in anticipating the worst-case scenario if The positive rate jumped high considering the challenges in handling Covid-19 from geographical aspects and the availability of laboratory facilities that have not been maximized.